MYORG is associated with recessive primary familial brain calcification. Issue 1 (15th November 2018) - Arkadir, David; Lossos, Alexander; Rahat, Dolev; Abu Snineh, Muneer; Schueler‐Furman, Ora; Nitschke, Silvia; Minassian, Berge A.; Sadaka, Yair; Lerer, Israela; Tabach, Yuval; Meiner, Vardiella
Abstract: Objective: To investigate the genetic basis of the recessive form of primary familial brain calcification and study pathways linking a novel gene with known dominant genes that cause the disease. Methods: Whole exome sequencing and Sanger‐based segregation analysis were used to identify possible disease causing mutations. Mutation pathogenicity was validated by structural protein modeling. Functional associations between the candidate gene, MYORG, and genes previously implicated in the disease were examined through phylogenetic profiling. Results: We studied nine affected individuals from two unrelated families of Middle Eastern origin. The median age of symptom onset was 29.5 years (range 21–57 years) and dysarthria was the most common presenting symptom. We identified in the MYORG gene, a homozygous c.1233delC mutation in one family and c.1060_1062delGAC mutation in another. The first mutation results in protein truncation and the second in deletion of a highly conserved aspartic acid that is likely to disrupt binding of the protein with its substrate. Phylogenetic profiling analysis of the MYORG protein sequence suggests co‐evolution with a number of calcium channels as well as other proteins related to regulation of anion transmembrane transport (False Discovery Rate, FDR < 10 −8 ) and with PDCD6IP, a protein interacting with PDGFR β which is known to be involved in the disease. Interpretation: MYORG mutations are linked to a recessive form of primary familial brain calcification. This association was recently described in patients of Chinese ancestry. We suggest the possibility that MYORG mutations lead to calcification in a PDGFR β ‐related pathway.